Pembuatan Katalog Produk Menggunakan Canva Sebagai Media Promosi Pada Warkop R. Basman Malang - Hafidh Ardiyansyah Suwandi; Dwi Sudjanarti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Warkop R.Basman promotes with word of mouth brochures and through whatsapp. The purpose of this research is to create promotional media in the form of a product catalog using Canva which displays a design according to the criteria for a good catalog at Warkop R.Basman Malang, to improve promotional media to consumers. This research uses the type of action research involving 15 respondents consisting of 1 owner, 2 marketing experts, 2 design experts, and 10 consumers. This action research was conducted up to cycle II. Based on the EPIC theory (Emphaty, Persuasion, Impact, and Communication) and from the results of distributing questionnaires, the average score is very effective. From the details of the EPIC average score, it can be concluded that the creation of promotional media through product catalogs made using Canva, can be declared very effective as promotional media.